An Integrated Approach of Efficiency Analysis for Violence-Response In One Stop Crisis Center (OSCC) - Ke Lin, Siew (None, 2025)
The study evaluated integrated performance measures for the efficiency and effectiveness analysis of the One Stop Crisis Center (OSCC) as a healthcare response for domestic violence survivors in Malaysia. The main objective is to develop an economic evaluation approach for violence-response in selected Malaysian OSCC using Data Envelopment Analysis (DEA). The findings reveal that most units in Centers A and C in the OSCC are experiencing increasing returns to scale, while most units in Center B are facing decreasing returns to scale in Model 1. This suggests the need for reshuffle or reallocation of healthcare providers to enhance technical efficiency and scale efficiency. Additionally, in Model 2, only slack values are identified in Centre A, suggesting that improving service quality is achievable by reducing response times. The Spearman rank correlation analysis reveals multisectorial coordination showed negative correlations between number of personnel and total response time in both ETD units and referral units, whereas supporting environment and attitude of staff showed positive correlations between number of personnel and total response time in referral units. Policy recommendations focus on targeted interventions to optimize staffing levels, support healthcare providers' resilience and foster a safety environment for DV survivors.